Identification of suitable sustainable agricultural intensification options for the Central Rift Valley, Ethiopia: Developing a multidisciplinary methodology for the Meki sub-basin - International Water Management Institute (International Water Management Institute, 2021)
Ethiopia has ambitious plans of expanding irrigation throughout the country to feed the growing population (FDRE 2011; NPC 2016). Due to population growth, landscapes in Ethiopia are facing increasing pressure from agriculture (e.g., Desta et al. 2020). The promotion of irrigation using shallow groundwater (Gowing et al. 2020; Tilahun et al. 2020) and better water lifting mechanisms (Gebregziabher 2012, 2019; Loulseged et al. 2011) is helping farmers to shift from only rain-fed agricultural production to utilizing irrigation during dry seasons and/or as a supplementary water source in the main rainy season.